Transition metal sulfide OER catalyst and preparation method thereof

The transition metal sulfide OER catalyst was prepared by microwave irradiation method, and complexing with graphene oxide support and thioacetamide was solved, and the problems of slow OER kinetics and high cost of precious metal catalysts were achieved, achieving efficient anode oxygen evolution reaction.

CN119640319APending Publication Date: 2025-03-18NORTHWEST UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510101540.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-22
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

Among the existing electrocatalytic water decomposition technologies, the anode oxygen evolution reaction (OER) kinetics are slow and require a large amount of energy to consume, which limits the widespread application of the technology, especially due to the scarcity and high cost of precious metal-based catalysts, the development of non-precious metal-based electrocatalysts is imminent.

Method used

The transition metal sulfide OER catalyst was quickly prepared by microwave irradiation method, graphene oxide was used as the support material, and the precursor powder was formed by complexing thioacetamide, and then microwave irradiation was performed under an inert atmosphere to form a transition metal sulfide composite nanomaterial.

Benefits of technology

The rapid preparation of the catalyst is achieved, with excellent photothermal conversion characteristics. By heating the catalyst locally, electron-to-movement mechanics are improved, OER performance is improved, and energy consumption is reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119640319A_ABST
    Figure CN119640319A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of catalysts, and particularly relates to a transition metal sulfide OER catalyst and a preparation method thereof.The preparation method comprises the following steps that soluble metal salt and graphene oxide dispersion liquid are evenly mixed at the normal temperature, and a precursor solution is obtained; the soluble metal salt is soluble Ni salt and soluble Fe salt; adding the metal precursor solution into a thioacetamide solution, stirring and drying to obtain precursor powder; and carrying out microwave irradiation treatment on the precursor powder in an argon atmosphere to obtain the transition metal sulfide composite nanomaterial. The rapid preparation of the sulfide is realized through a microwave irradiation method, and the preparation process is simple. The photothermal conversion characteristic is utilized, the catalyst is efficiently and locally heated, the endothermic enthalpy change of the OER is counteracted, the electron transfer kinetics is improved, and the OER performance is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of catalysts, and in particular relates to a transition metal sulfide OER catalyst and a preparation method thereof. Background Art

[0002] As a renewable and clean energy source, hydrogen has always attracted much attention due to its advantages such as high combustion calorific value, light weight, clean and pollution-free. Electrocatalytic water splitting technology can produce green hydrogen through renewable electricity and is considered to be the simplest and most effective method for hydrogen production. The electrolysis of water to produce hydrogen involves two half reactions, including the cathode hydrogen evolution reaction (HER) and the anode oxygen evolution reaction (OER). Among them, OER has a high redox potential and slow kinetics, which requires a lot of energy, limiting the large-scale application of electrocatalytic water splitting technology. In order to break through this bottleneck, it is necessary to design high-performance electrocatalysts that can accelerate the OER process. At present, IrO 2 and RuO 2 Precious metal-based catalysts, represented by , exhibit excellent OER performance. However, due to their scarcity and high cost, non-precious metal-based electrocatalysts are still in great need of exploration to promote the widespread application of electrocatalytic water splitting technology.

[0003] Transition metal sulfides have been widely developed as promising OER electrocatalysts due to their abundant reserves, outstanding electronic structures, and good electrical conductivity. However, the traditional preparation methods of sulfides are complicated and the OER activity needs to be improved. Summary of the invention

[0004] In order to solve the above technical problems, the present invention provides a transition metal sulfide OER catalyst and a preparation method thereof, which realizes the rapid preparation of sulfide by microwave irradiation, and the prepared transition metal sulfide composite nanomaterial has excellent photothermal conversion characteristics. By locally heating the catalyst of the present invention, it has excellent OER activity.

[0005] A method for preparing a transition metal sulfide OER catalyst comprises the following steps: The soluble metal salt and the graphene oxide dispersion are uniformly mixed at room temperature, and the metal ions are adsorbed on the surface of the graphene oxide through electrostatic action to obtain a precursor solution; the soluble metal salt is a soluble Ni salt and a soluble Fe salt.

[0006] The metal precursor solution is added into the thioacetamide solution, stirred, the metal ions are complexed with the thioacetamide, and the precursor powder is obtained after drying.

[0007] The precursor powder is subjected to microwave irradiation treatment in an inert atmosphere, and is sulfurized under microwave irradiation heating conditions to obtain a transition metal sulfide OER catalyst.

[0008] In a preferred embodiment of the present invention, in the transition metal sulfide composite nanomaterial, the molar ratio of Ni to Fe is 2 to 4:1.

[0009] In a preferred embodiment of the present invention, in the precursor solution, the total concentration of the soluble Ni salt and the soluble Fe salt is 0.01 g / mL to 0.04 g / mL.

[0010] In a preferred embodiment of the present invention, the graphene oxide dispersion is a dispersion of graphene oxide obtained by ultrasonic treatment of distilled water, and the concentration of the graphene oxide dispersion is 0.001 g / mL to 0.003 g / mL.

[0011] In a preferred embodiment of the present invention, the thioacetamide solution is a solution obtained by dissolving thioacetamide in distilled water, and the concentration of the thioacetamide solution is 0.06 g / mL to 0.08 g / mL.

[0012] In a preferred embodiment of the present invention, the molar ratio of thioacetamide to the soluble metal salt is 2.4-3.1:1.

[0013] In a preferred embodiment of the present invention, the power of the microwave radiation is 600W to 800W, and the irradiation time is 75s to 165s.

[0014] The present invention provides an OER electrocatalyst prepared by the above preparation method. The OER electrocatalyst is a nanoparticle with a diameter of 10nm to 100nm. The OER electrocatalyst catalyzes the anode oxygen evolution reaction under near-infrared light irradiation, which can improve the catalytic activity.

[0015] Compared with the prior art, the present invention has the following beneficial effects: The surface of graphene oxide contains abundant oxygen-containing functional groups, and metal ions are adsorbed on the surface of graphene oxide by electrostatic action to obtain a precursor solution. Graphene oxide is conductive and has a large specific surface area and good physicochemical stability. Using it as a supporting material can further improve the electrochemical performance. Thioacetamide solution is added to the above-mentioned precursor solution, and the metal ions are complexed with it, and a precursor powder is obtained after drying. The obtained precursor powder is subjected to microwave irradiation treatment, and a high temperature can be reached in a short time. Sulfurization is performed at high temperature to generate transition metal sulfide composite nanomaterials. The present invention realizes the rapid preparation of sulfides by microwave irradiation method, and the preparation process is simple. The prepared catalyst has photothermal conversion characteristics. By locally heating the catalyst, the endothermic enthalpy change of OER is offset, the electron transfer kinetics are improved, and the OER performance is improved. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1 This is the XRD pattern of the catalyst sample prepared in Example 1 of the present invention.

[0017] Figure 2 This is the SEM image of the catalyst sample prepared in Example 1 of the present invention.

[0018] Figure 3 This is a linear sweep voltammogram of OER of the catalyst sample prepared in Example 1 of the present invention in 1M KOH solution.

[0019] Figure 4 This is a linear sweep voltammogram of OER of the catalyst sample prepared in Example 2 of the present invention in 1 M KOH solution.

[0020] Figure 5 This is a linear sweep voltammogram of OER of the catalyst sample prepared in Example 3 of the present invention in 1 M KOH solution.

[0021] Figure 6 This is a linear sweep voltammogram of OER of the catalyst sample prepared in Example 4 of the present invention in 1 M KOH solution.

[0022] Figure 7 This is a linear sweep voltammogram of OER of the catalyst sample prepared in Example 5 of the present invention in 1 M KOH solution.

[0023] Figure 8 This is a linear sweep voltammogram of OER of the catalyst sample prepared in Example 6 of the present invention in 1 M KOH solution.

[0024] Fig. 9 This is a linear sweep voltammogram of OER of the catalyst sample prepared in Example 7 of the present invention in 1 M KOH solution.

[0025] Fig.10 Linear sweep voltammogram of OER of the catalyst sample prepared in Example 8 (the molar ratio of Ni to Fe is 2:1) in 1 M KOH solution.

[0026] Fig.11 Linear sweep voltammogram of OER of the catalyst sample prepared in Example 9 (the molar ratio of Ni to Fe is 4:1) in 1 M KOH solution. DETAILED DESCRIPTION

[0027] In order to enable those skilled in the art to better understand the technical solution of the present invention and implement it, the present invention is further described below in conjunction with specific embodiments and drawings, but the embodiments are not intended to limit the present invention. The experimental methods and detection methods described in the following embodiments are conventional methods unless otherwise specified; the reagents and materials described are all commercially available unless otherwise specified.

[0028] The present invention provides a method for preparing a transition metal sulfide OER catalyst, comprising the following steps: The soluble metal salt and the graphene oxide dispersion are uniformly mixed at room temperature to obtain a precursor solution; the soluble metal salt is a soluble Ni salt and a soluble Fe salt.

[0029] The metal precursor solution is added into the thioacetamide solution, stirred, and dried to obtain the precursor powder.

[0030] The precursor powder is subjected to microwave irradiation treatment in an argon atmosphere to obtain a transition metal sulfide composite nanomaterial.

[0031] The surface of graphene oxide contains abundant oxygen-containing functional groups. Metal ions are adsorbed on the surface of graphene oxide by electrostatic action to obtain a precursor solution. Graphene oxide is conductive and has a large specific surface area and good physical and chemical stability. Using it as a supporting material can further improve the electrochemical performance. Thioacetamide solution is added to the above-mentioned precursor solution, and the metal ions are complexed with it. After drying, a precursor powder is obtained. The obtained precursor powder is subjected to microwave irradiation treatment to reach a high temperature in a short time. Sulfidation at high temperature generates transition metal sulfide composite nanomaterials. The traditional sulfide preparation method has complex steps and the OER activity needs to be improved. Increasing the temperature is an effective strategy to improve the electrocatalytic performance. However, the traditional heating method requires the use of a heating device to heat the entire reaction system, which not only increases the complexity and cost, but also reduces the durability of water decomposition. In contrast, the photothermal conversion effect can provide local efficient heating. The OER electrocatalyst with a photothermal effect can achieve self-heating under light. The surface temperature of the electrocatalyst can be controlled by adjusting the intensity and wavelength of the incident light. The present invention realizes the rapid preparation of sulfide by microwave irradiation method, the preparation process is simple, the prepared catalyst has the characteristic of photothermal conversion, and the endothermic enthalpy change of OER is offset by local heating of the catalyst, the electron transfer kinetics is improved, and the OER performance is improved.

[0032] The present invention will be specifically described below by the following examples.

[0033] Example 1 (1) Disperse 60 mg of graphene oxide in 30 mL of distilled water and disperse by ultrasonic in an ice-water bath for 1 h to form a uniform dispersion; (2) adding 0.72 g of nickel nitrate and 0.33 g of ferric nitrate to the solution of step (1), stirring at room temperature to obtain a precursor solution; (3) Dissolve 0.7 g of thioacetamide in 10 mL of distilled water, add the mixture to the precursor solution in step (2), stir for 2 h, and then vacuum dry to obtain a precursor powder; (4) The precursor powder obtained in (3) is placed in a quartz bottle and subjected to 800W microwave irradiation for 120s under an argon atmosphere to obtain a transition metal sulfide composite nanomaterial. The transition metal sulfide composite nanomaterial is in the form of nanoparticles with a diameter of 10 to 100 nm, such as Figure 1 and Figure 2 shown.

[0034] The OER reaction performance test of the transition metal sulfide composite nanomaterial prepared in Example 1 is as follows: Weigh 2.5 mg of the catalyst sample (the catalyst prepared in Example 1 of the present invention, hereinafter referred to as the catalyst sample) and add it to a solution containing 480 μL of isopropanol and 20 μL of Naifon solution (5 wt%), and ultrasonically treat for 30 min to evenly disperse the catalyst. Take 5 μL of the evenly dispersed sample solution to the surface of the glassy carbon electrode, dry it, and test it using a standard three-electrode system, with a graphite rod as the counter electrode, mercury / mercuric oxide as the reference electrode, and 1 M KOH as the electrolyte. The scan rate of the linear voltammetric curve is 5 mV / s.

[0035] Test results: Figure 3 As shown, when 100 mA·cm -2 At a current density of , the overpotential is 271mV.

[0036] Example 2 (1) Disperse 60 mg of graphene oxide in 30 mL of distilled water and disperse by ultrasonic in an ice-water bath for 1 h to form a uniform dispersion; (2) adding 0.72 g of nickel nitrate and 0.33 g of ferric nitrate to the solution of step (1), stirring at room temperature to obtain a precursor solution; (3) Dissolve 0.7 g of thioacetamide in 10 mL of distilled water, add the mixture to the precursor solution in step (2), stir for 2 h, and then vacuum dry to obtain a precursor powder; (4) The precursor powder obtained in (3) was placed in a quartz bottle and subjected to 800 W microwave irradiation for 75 seconds under an argon atmosphere to obtain a transition metal sulfide composite nanomaterial.

[0037] The OER reaction performance test was performed on the transition metal sulfide composite nanomaterial prepared in Example 2, and the specific implementation method was the same as that in Example 1.

[0038] Test results: Figure 4 As shown, when 100 mA·cm -2 At a current density of , the overpotential is 346 mV.

[0039] Example 3 (1) Disperse 60 mg of graphene oxide in 30 mL of distilled water and disperse by ultrasonic in an ice-water bath for 1 h to form a uniform dispersion; (2) adding 0.72 g of nickel nitrate and 0.33 g of ferric nitrate to the solution of step (1), stirring at room temperature to obtain a precursor solution; (3) Dissolve 0.7 g of thioacetamide in 10 mL of distilled water, add the mixture to the precursor solution in step (2), stir for 2 h, and then vacuum dry to obtain a precursor powder; (4) The precursor powder obtained in (3) was placed in a quartz bottle and subjected to 800 W microwave irradiation for 165 s under an argon atmosphere to obtain a transition metal sulfide composite nanomaterial.

[0040] The transition metal sulfide composite nanomaterial prepared in Example 3 was tested for OER reaction performance, and the specific implementation method was the same as that in Example 1.

[0041] Test results: Figure 5 As shown, when 100 mA·cm -2 At a current density of , the overpotential is 313mV Example 4 In view of the excellent performance of transition metal sulfide composite nanomaterials in electrocatalytic oxygen evolution, we loaded the transition metal sulfide composite nanomaterials prepared in Example 1 on nickel fiber felt (NFF) to further optimize the electrocatalytic oxygen evolution performance. The OER reaction performance of the transition metal sulfide composite nanomaterials loaded on NFF was tested as follows:

[0042] Weigh 5 mg of the catalyst sample and add it to a solution containing 480 μL of isopropanol and 20 μL of Naifon solution (5 wt%). Ultrasonic treatment was performed for 30 min to make the catalyst evenly dispersed. Take 100 μL of the evenly dispersed sample solution and drop it onto NFF (0.5 x 1.5 cm) treated with ethanol and dilute hydrochloric acid. After drying, the standard three-electrode system was used for testing. The graphite rod was used as the counter electrode, mercury / mercuric oxide was used as the reference electrode, and 1M KOH was used as the electrolyte. The area immersed in the solution was 0.5 x 0.5 cm = 0.25 cm 2 The scanning rate of the linear voltammetric curve was 5 mV / s.

[0043] Test results: Figure 6 As shown, when 100 mA·cm -2 At a current density of , the overpotential is 260mV.

[0044] Example 5 In view of the fact that the thermal effect can locally heat the catalyst and improve the electrocatalytic oxygen evolution performance, we further irradiated the transition metal sulfide composite nanomaterial loaded on NFF prepared in Example 4 with near-infrared light to locally heat the catalyst during the oxygen evolution performance test. The details are as follows:

[0045] Weigh 5 mg of the catalyst sample and add it to a solution containing 480 μL of isopropanol and 20 μL of Naifon solution (5 wt%). Ultrasonic treatment was performed for 30 min to make the catalyst evenly dispersed. Take 100 μL of the evenly dispersed sample solution and drop it onto NFF (0.5 x 1.5 cm) treated with ethanol and dilute hydrochloric acid. After drying, the standard three-electrode system was used for testing. The graphite rod was used as the counter electrode, mercury / mercuric oxide was used as the reference electrode, and 1M KOH was used as the electrolyte. The area immersed in the solution was 0.5 x 0.5 cm = 0.25 cm 2 During the test, near-infrared light was used to illuminate the area immersed in the solution. The power of the near-infrared light was 1.78W, and the scanning rate of the linear voltammetric curve was 5mV / s.

[0046] Test results: Figure 7 As shown, when 100 mA·cm -2 At a current density of , the overpotential is 237 mV.

[0047] Example 6 The transition metal sulfide composite nanomaterial loaded on NFF prepared in Example 4 was irradiated with near infrared light to locally heat the catalyst during the oxygen evolution performance test. The details are as follows:

[0048] Weigh 5 mg of the catalyst sample and add it to a solution containing 480 μL of isopropanol and 20 μL of Naifon solution (5 wt%). Ultrasonic treatment was performed for 30 min to make the catalyst evenly dispersed. Take 100 μL of the evenly dispersed sample solution and drop it onto NFF (0.5 x 1.5 cm) treated with ethanol and dilute hydrochloric acid. After drying, the standard three-electrode system was used for testing. The graphite rod was used as the counter electrode, mercury / mercuric oxide was used as the reference electrode, and 1M KOH was used as the electrolyte. The area immersed in the solution was 0.5 x 0.5 cm = 0.25 cm 2 During the test, near-infrared light was used to illuminate the area immersed in the solution. The power of the near-infrared light was 2.69 W, and the scanning rate of the linear voltammetric curve was 5 mV / s.

[0049] Test results: Figure 8 As shown, when 100 mA·cm -2 At a current density of , the overpotential is 227mV.

[0050] Example 7 The transition metal sulfide composite nanomaterial loaded on NFF prepared in Example 4 was irradiated with near infrared light to locally heat the catalyst during the oxygen evolution performance test. The details are as follows:

[0051] Weigh 5 mg of the catalyst sample and add it to a solution containing 480 μL of isopropanol and 20 μL of Naifon solution (5 wt%). Ultrasonic treatment was performed for 30 min to make the catalyst evenly dispersed. Take 100 μL of the evenly dispersed sample solution to NFF (0.5 x 1.5 cm) treated with ethanol and dilute hydrochloric acid, respectively. After drying, the standard three-electrode system was used for testing, with a graphite rod as the counter electrode, mercury / mercuric oxide as the reference electrode, and 1 M KOH as the electrolyte. The area immersed in the solution was 0.5 x 0.5 cm = 0.25 cm 2 During the test, near-infrared light was used to illuminate the area immersed in the solution. The power of the near-infrared light was 3.77W, and the scanning rate of the linear voltammetric curve was 5mV / s.

[0052] Test results, such as Fig. 9 As shown, when 100 mA·cm -2 At a current density of , the overpotential is 216 mV.

[0053] Example 8 (1) Disperse 60 mg of graphene oxide in 30 mL of distilled water and disperse by ultrasonic in an ice-water bath for 1 h to form a uniform dispersion; (2) adding 0.65 g of nickel nitrate and 0.45 g of ferric nitrate to the solution of step (1), stirring at room temperature to obtain a precursor solution; (3) Dissolve 0.7 g of thioacetamide in 10 mL of distilled water, add the mixture to the precursor solution in step (2), stir for 2 h, and then vacuum dry to obtain a precursor powder; (4) The precursor powder obtained in (3) was placed in a quartz bottle and subjected to 800 W microwave irradiation for 120 s under an argon atmosphere to obtain a transition metal sulfide composite nanomaterial.

[0054] The OER reaction performance of the transition metal sulfide composite nanomaterial prepared in Example 8 was tested.

[0055] Test results: Fig.10 As shown, when 100 mA·cm -2 At a current density of , the overpotential is 298mV.

[0056] Example 9 (1) Disperse 60 mg of graphene oxide in 30 mL of distilled water and disperse by ultrasonic in an ice-water bath for 1 h to form a uniform dispersion; (2) adding 0.77 g of nickel nitrate and 0.27 g of ferric nitrate to the solution of step (1), stirring at room temperature to obtain a precursor solution; (3) Dissolve 0.7 g of thioacetamide in 10 mL of distilled water, add the mixture to the precursor solution in step (2), stir for 2 h, and then vacuum dry to obtain a precursor powder; (4) The precursor powder obtained in (3) was placed in a quartz bottle and subjected to 800 W microwave irradiation for 120 s under an argon atmosphere to obtain a transition metal sulfide composite nanomaterial.

[0057] The transition metal sulfide composite nanomaterial prepared in Example 9 was tested for its OER reaction performance.

[0058] Test results: Fig.11 As shown, when 100 mA·cm -2 At a current density of , the overpotential is 316 mV.

[0059] Obviously, those skilled in the art can make various changes and modifications to the present invention without departing from the spirit and scope of the present invention. Thus, if these modifications and variations of the present invention fall within the scope of the claims of the present invention and their equivalents, they are also intended to be included.

Claims

1. A method for preparing a transition metal sulfide OER catalyst, characterized in that: The following steps are involved: The soluble metal salt and the graphene oxide dispersion are uniformly mixed at room temperature, and the metal ions are adsorbed on the surface of the graphene oxide by electrostatic action to obtain a precursor solution; the soluble metal salt is a soluble Ni salt and a soluble Fe salt; The metal precursor solution and the thioacetamide solution are mixed and stirred to allow the metal ions to complex with the thioacetamide, and then dried to obtain a precursor powder; The precursor powder is subjected to microwave irradiation treatment in an inert atmosphere, and is sulfurized under microwave irradiation heating conditions to obtain a transition metal sulfide OER catalyst.

2. The preparation method according to claim 1, characterized in that: In the transition metal sulfide OER catalyst, the molar ratio of Ni element to Fe element is 2 to 4:

1.

3. The preparation method according to claim 1, characterized in that: In the precursor solution, the total concentration of the soluble Ni salt and the soluble Fe salt is 0.01 g / mL to 0.04 g / mL.

4. The preparation method according to claim 1, characterized in that: The graphene oxide dispersion is a dispersion of graphene oxide in water, and the concentration of the graphene oxide dispersion is 0.001 g / mL to 0.003 g / mL.

5. The preparation method according to claim 1, characterized in that: The thioacetamide solution is a solution obtained by dissolving thioacetamide in water, and the concentration of the thioacetamide solution is 0.06 g / mL to 0.08 g / mL.

6. The preparation method according to claim 1, characterized in that: The molar ratio of thioacetamide to the soluble metal salt is 2.4-3.1:

1.

7. The preparation method according to claim 1, characterized in that: The power of the microwave radiation is 600W to 800W, and the irradiation time is 75s to 165s.

8. A transition metal sulfide OER catalyst prepared according to the preparation method according to any one of claims 1 to 7.

9. The transition metal sulfide OER catalyst according to claim 8, characterized in that The transition metal sulfide OER catalyst is a nanoparticle with a diameter of 10nm to 100nm.

10. The transition metal sulfide OER catalyst according to claim 8, characterized in that Catalyzes the anodic oxygen evolution reaction under near-infrared light irradiation.